2014
DOI: 10.1016/j.molonc.2014.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule growth inhibitors of human oncogenic gammaherpesvirus infected B‐cells

Abstract: Epstein-Barr virus (EBV) and Kaposi’s sarcoma associated herpesvirus (KSHV) are two human gammaherpesviruses associated with a broad spectrum of B-cell lymphomas, most acutely in immuno-compromised populations. However, there are no drugs which specifically target KSHV or EBV-associated lymphomas. To identify small molecules which selectively inhibit the growth of EBV or KSHV-associated B-cell lines, we performed a fluorescence based high-throughput screen on multiple stable GFP expressing virus-infected or un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…This prompted us to follow-up on our current data above to more closely understand the link between p21 and NF-kB in KSHV positive cells. Interestingly, in other studies we also observed that small molecules inhibitors targeted EBV and KSHV lymphoma cells through the NF-kB pathway [ 58 ]. Here we analyzed BC-3 cells in the presence of a SNAIL inhibitor, as a KSHV positive cell line compared to the KSHV negative cell line BJAB ( Fig 10A and 10B ).…”
Section: Resultsmentioning
confidence: 87%
“…This prompted us to follow-up on our current data above to more closely understand the link between p21 and NF-kB in KSHV positive cells. Interestingly, in other studies we also observed that small molecules inhibitors targeted EBV and KSHV lymphoma cells through the NF-kB pathway [ 58 ]. Here we analyzed BC-3 cells in the presence of a SNAIL inhibitor, as a KSHV positive cell line compared to the KSHV negative cell line BJAB ( Fig 10A and 10B ).…”
Section: Resultsmentioning
confidence: 87%
“…Moreover, many cancers are targeted using Aurora kinase and Pim1 inhibitors for reducing tumor burden. A prognostic approach where using small molecules inhibitors targeting key signaling pathways in these viral infected cells may be useful in combination with kinase inhibitors [ 371 ]. Moreover, in vivo studies will be critical for validation of these strategies followed by clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have successfully identified several small molecules inhibitors (NSC65381, NSC10010, NSC16553, and NSC1881) that were able to kill virus positive LCLs as well as EBV negative BL cells (Dzeng et al, 2015). We have also demonstrated that c-Myc and NF-kB are the major signaling molecules targeted through these inhibitors to kill virus positive cells (Dzeng et al, 2015).…”
Section: Treatment Of Ebv Associated Diseasesmentioning
confidence: 99%
“…We have also demonstrated that c-Myc and NF-kB are the major signaling molecules targeted through these inhibitors to kill virus positive cells (Dzeng et al, 2015). Earlier, arsenic trioxide (As2O3) and sodium arsenite (NaAsO2) were also shown to induce cell death in P3HR1 cells (Zebboudj et al, 2014).…”
Section: Treatment Of Ebv Associated Diseasesmentioning
confidence: 99%